Distribution of p63, a novel myoepithelial marker, in fine-needle aspiration biopsies of the breast: an analysis of 82 samples - Reis Filho, Jorge S. (2003)
BACKGROUND. The presence of myoepithelial cells (MECs) in fine-needle aspiration biopsies (FNAB) of the breast constitute an important criterion used to diagnose benign breast lesions. However, MECs sometimes have a distorted cytomorphology, and most of the previously evaluated myoepithelial markers do not have satisfactory sensitivity and specificity. p63, a recently characterized p53 homolog, is a nuclear transcription factor that is expressed in basal cells of multilayered epithelia and myoepithelial cells of the breast. The authors analyzed the immunocytochemical distribution of p63 in a series of 82 breast FNABs (30 benign lesions and 52 malignant breast lesions). METHODS. Eighty-two archival, Papanicolaou-stained smears of breast lesions were retrieved from the files of the authors’ institutions. Immunocytochemistry was performed according to the streptavidin-biotin-peroxidase complex technique using the antibody 4A4 (against all p63 isoforms). Two pathologists evaluated the distribution of p63 positive cells. Only nuclear reactivity was considered specific. RESULTS. In benign lesions, p63 decorated the nuclei of MECs in all samples. p63 also stained naked nuclei in fibroadenomas. In malignant lesions, p63 was positive in MECs overlying malignant cell clusters in all 8 samples of ductal carcinoma in situ (DCIS), in 9 of 16 samples of pure invasive carcinomas (IC), and in 16 of 20 samples that contained both DCIS and IC. In 18 samples (36%), a variable population of p63 positive, malignant cells was observed. p63 failed to decorate stromal, neural, adipocytic, and smooth muscle cells in all samples. CONCLUSIONS. p63 is a reliable nuclear marker of MECs in breast aspirates. Regardless of the fact that variable proportions of p63 positive, malignant cells were observed in 36% of breast carcinoma aspirates, p63 may be a useful adjunct antibody to confirm the presence of MECs in FNABs of benign breast lesions.